ANALYSIS OF COST AND CASTING TIME WITH CONVENTIONAL AND PRECAST METHODS ON THE CITEREUP FLYOVER CONSTRUCTION PROJECT - Ari Yulitasari; Alip Prajoko; Abdul Mubarak; Edison Hatoguan Manurung (International Journal of Multidisciplinary Research and Literature, 2023)
The concrete manufacturing process, also known as casting, is the final stage that determines the success of a flyover construction project. The benchmark lies in the casting method which of course has a direct effect on resource efficiency, processing time, budget, and quality. Generally, the process of casting concrete in flyover construction projects in Indonesia uses the conventional method in which the process is carried out and cast in situ. However, the development of science and the paradigm of efficiency in the dimensions of flyover construction projects has given birth to a new method in which the concrete hardening process can be carried out elsewhere and made precast.The conventional method and the precast method are now the best alternative by taking into account aspects of cost, quality and time which are considered for efficiency in flyover construction projects. For this reason, the researchers analyzed the efficiency of the Citeureup flyover construction project using the concrete casting method used in the process